The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21273/horttech04617-20
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Chambourcin’ Winegrape on Nematode-resistant Rootstocks in Missouri

Abstract: One of the most popular winegrapes (Vitis sp.) for red wine production in the midwestern United States is ‘Chambourcin’, a French-American hybrid. It is typically produced on own-rooted vines in the region, but the potential benefits of grafting it to improved rootstocks are becoming better-known. Nematodes present occasional serious winegrape production challenges in the midwestern United States, and are capable of transmitting pathogenic viruses. New rootstocks developed by University of California, Davis (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Not less importantly, the high content of V. berlandieri and V. rupestris ancestries in its parentage, considering the high resistance of these American vines to Phylloxera vastatrix (Table 2), suggests that Chambourcin can be produced on own-rooted vines, even though the potential benefits of grafting it to improved rootstocks is well recognized [38,39]. In this regard, it should be noticed that the yield (11.6 kg grape/vine), in the case of ownrooted Chambourcin vines, was reported to be comparable to that recorded for grafted vines [40]. Therefore, viticulture, thanks to hybrid grapes like Chambourcin, could become more sustainable not only from an environmental point of view (avoiding chemicals accumulation in soil) but also considering a merely economic perspective, as it does not necessarily require grafted vines.…”
Section: Pedigree Of Chambourcin: From Molecular Markers and Breeders...mentioning
confidence: 92%
See 1 more Smart Citation
“…Not less importantly, the high content of V. berlandieri and V. rupestris ancestries in its parentage, considering the high resistance of these American vines to Phylloxera vastatrix (Table 2), suggests that Chambourcin can be produced on own-rooted vines, even though the potential benefits of grafting it to improved rootstocks is well recognized [38,39]. In this regard, it should be noticed that the yield (11.6 kg grape/vine), in the case of ownrooted Chambourcin vines, was reported to be comparable to that recorded for grafted vines [40]. Therefore, viticulture, thanks to hybrid grapes like Chambourcin, could become more sustainable not only from an environmental point of view (avoiding chemicals accumulation in soil) but also considering a merely economic perspective, as it does not necessarily require grafted vines.…”
Section: Pedigree Of Chambourcin: From Molecular Markers and Breeders...mentioning
confidence: 92%
“…Moreover, when grapevines are grafted to a rootstock, that is typically a vine resistant to Phylloxera vastatrix but not a productive variety, and the vine is damaged (during particularly cold winters or following fires-very common in South Italy-or other destructive events) below the graft union, the rootstock and not the desired grape cultivar will send up new growth the next year. Conversely, if a grapevine is planted on its own roots, as can be done with the Chambourcin [40], and killed to the ground level, the next year the desired cultivar will reappear and the vineyard can be back in production soon [41].…”
Section: Pedigree Of Chambourcin: From Molecular Markers and Breeders...mentioning
confidence: 99%
“…Soil pH was evaluated midstudy (June 2013), and indicated an excellent pH of 6.3. Significant additional details on climate, vineyard establishment, pest management, soil fertility management, and irrigation are outlined in Thomas et al (2017Thomas et al ( , 2020.…”
Section: Methodsmentioning
confidence: 99%
“…It is a complex interspecific French-American hybrid based on Seibel hybrids, released in 1963 (Robinson et al 2012;University of California, Davis 2020). Despite having sufficient phylloxera tolerance to survive own-rooted, it is sometimes grafted with the assumption that growth and quality parameters are improved (Thomas et al 2020(Thomas et al , 2017. Because the effects of particular rootstocks on different winegrape cultivar production and quality across diverse environments have not been widely tested, it is important to understand the scion cultivar-rootstock-environment interaction (Santiago et al 2007).…”
mentioning
confidence: 99%